Persepsi Mahasiswa Universitas Muhammadiyah Palopo terhadap Pelaksanaan Pembelajaran Daring Saat Pandemi Covid-19 - Saman Saman (MANAZHIM, 2021)
This research is a qualitative descriptive study which includes data collection, data reduction, data presentation, and conclusion drawing. The population in this study were all undergraduate students of the Muhammadiyah University of Palopo for all the subjects taught by the author. Samples were taken using purposive sampling technique which is only aimed at students who take courses that are taught by the author in several majors, one of which is the accounting department. The data in this study were obtained through a questionnaire that was filled out online by students using Google Form. The questionnaire used was adapted from the practical course service satisfaction questionnaire issued by the Center for Learning Development and Education Quality Assurance (P4MP) Bengkalis State Polytechnic, where the questionnaire consisted of three aspects of assessment namely (a) aspects of teaching and learning, (b) aspects of competence lecturers, and (c) infrastructure aspects. From the results of the analysis, the results obtained for the teaching and learning aspects of the majority (110 or as many as 68%) of students thought that online learning could be accessed well, besides the results of manual calculations using the Ms. application. Office Excel obtained an average result for the teaching and learning aspects of 3.28